Laser‐Induced Cooperative Transition in Molecular Electronic Crystal (Adv. Mater. 39/2021). Issue 39 (1st October 2021) - Hu, Yong; Adhikari, Dasharath; Tan, Andrew; Dong, Xi; Zhu, Taishan; Wang, Xiaoyu; Huang, Yulong; Mitchell, Travis; Yao, Ziheng; Dasenbrock‐Gammon, Nathan; Snider, Elliot; Dias, Ranga P.; et al.
Abstract : Supramolecular Electronic Crystals The cooperative tuning of a supramolecular electronic crystal enables access to a long‐lived hidden conducting phase with a broad temperature range from 2 to 360 K, through a pulsed electromagnetic field. In article number 2103000, Shenqiang Ren and co‐workers demonstrate a a dynamic and cooperative phase in K‐TCNQ, with the control of pulsed electromagnetic excitation. A dedicated charge–spin–lattice decoupling is required to activate and subsequently stabilize the non‐equilibrium phase.